Development and Congenital Anomalies of the Pancreas. (14th May 2011) - Tadokoro, Hiroyuki; Takase, Masaru; Nobukawa, Bunsei
Abstract : Understanding how the pancreas develops is essential to understand the pathogenesis of congenital pancreatic anomalies. Recent studies have shown the advantages of investigating the development of frogs, mice, and chickens for understanding early embryonic development of the pancreas and congenital anomalies, such as choledochal cysts, anomalous pancreaticobiliary junction, annular pancreas, and pancreas divisum. These anomalies arise from failure of complete rotation and fusion during embryogenesis. There are many theories in the etiology of congenital anomalies of the pancreas. We review pancreas development in humans and other vertebrates. In addition, we attempt to clarify how developmental failure is related to congenital pancreatic anomalies.